Evaluation of the injured runner - Magrum, E.; Wilder, R. P. (Clinics in Sports Medicine, 2010)
The evaluation of the injured runner emphasizes the identification of intrinsic and extrinsic risk factors in addition to establishing injury-specific diagnosis. The history emphasizes identification of contributory changes in training regimen or technique. The physical examination includes a biomechanical and functional screening to identify related imbalances in posture, alignment, strength, flexibility, and lower quarter stability. Each runner is also observed walking and running because running is a dynamic activity, and subtle abnormalities not evident during static or open chain examination may become evident upon functional and dynamic evaluation. This comprehensive, running-specific approach to diagnosis assists the clinician in developing optimum rehabilitation programs.